(untitled) (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2023)
Climate change affects agriculture through its impact on plant growth, development and yield. Research on indications of climate change and its impact on rice production in Indonesia in South Sumatra This research aims to examine climate change and its impacts on rice production in Indonesia. This study uses data from temperature, bulk rain, agroclimate, and rice production as well as socio-economic data. Methodology This research is an explanatory descriptive study using the concept of risk assessment where risk (risk) is a function of danger (hazard) and vulnerability (vulnerability). Study results shows that in Indonesia there has been climate change with indications of increasing temperature, changes in rainfall patterns, changes in hitergraphs, and changes in Oldeman classification.